Implementación del modelo de peplau en las intervenciones de enfermería y su relación con la prevención de diabetes mellitus tipo ii en el subcentro de salud Enrique Ponce Luque. Babahoyo. Los Ríos. Primer semestre 2018. - Díaz Sánchez, María Fernanda (2018)
Introduction: Efficient nursing care of patients with Type II Diabetes Mellitus implies a coordinated and multidisciplinary work in order to offer an improvement in the continuity of the care.Objective: Analyze the implementation of the Peplau model and its relation with the interventions of nursing in the prevention of Type II Diabetes Mellitus in the Enrique Ponce Luque health center. Material and methods: non-probabilistic sampling is used, a survey was applied to 15 professionals. The qualitative variables were taken into account: implementation of the Peplau model, nursing interventions, prevention of type II diabetes mellitus and secondary variables. The technique for collecting information was the survey. Results: The implementation of the Peplau model allowed an approach to the knowledge and application of the model in the prevention of type II diabetes mellitus. From the nursing interventions, it was possible to identify the skills in the management of preventive practices. Conclusions: the sociodemographic profile young people between 18 and 25 years old, female gender, married, licensed. Adequate interrelation with the patient is guaranteed, not all patients demonstrate confidence to express their needs, communicate medical procedures, educate themselves, advise to apply self-care, sometimes promote independence, manage stress and educate risk patients; in the implementation the application of the identification and resolution phase is affected, in any case, skills and greater autonomy of the patient are enhanced.